Resilience of coastal wetlands to extreme hydrologic events in Apalachicola Bay - Subrina Tahsin; Stephen C. Medeiros; Arvind Singh (Geophysical Research Letters)
Abstract Extreme hydrologic events such as hurricanes and droughts continuously threaten wetlands which provide key ecosystem services in coastal areas. The recovery time for vegetation after impact from these extreme events can be highly variable depending on the hazard type and intensity. Apalachicola Bay in Florida is home to a rich variety of saltwater and freshwater wetlands and is subject to a wide range of hydrologic hazards. Using spatiotemporal changes in Landsat‐based empirical vegetation indices, we investigate the impact of hurricane and drought on both freshwater and saltwater wetlands from year 2000 to 2015 in Apalachicola Bay. Our results indicate that saltwater wetlands are more resilient than freshwater wetlands and suggest that in response to hurricanes, the coastal wetlands took almost a year to recover, while recovery following a drought period was observed after only a month.